Against the ruling political power. Clandestine activities and pirates in Europe from 1933 to the present - Faragó, László (Acta Scientiarum Socialium, 2011)
The paper analyzes the unlicensed radios, how they were formed and what the motivation for their formation was. The ideology of pirates is connected with the idea of free broadcasting and liberalism, and it contributed to a widening of the social discourse. Unlicensed radios have several times promoted social change and wrung the required laws from authorities. Pirates or clandestine radios have played an important part in international political propagandizing. In Hungary, pirates have played a significant role in changing the social structure as well as in changing the hegemony of program providers. Pirates have contributed to structural changes in local publicity. Since these radios have started, Hungarian society has begun to accept the minority: independent thinkers and minority groups such as homosexuals more easily. Radio Sirius seemed to be piratical in the eyes of authorities, but it was the local government’s partner at the same time.
Keywords: clandestine activities; pirate radios; history of radio broadcasting